Pentingnya Perencanaan Karier Terhadap Pengambilan Keputusan Karier - Maria Ni Komang Ayu; I Gde Dhika Widarnandana; Diah Widiawati Retnoningtias (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The results of previous studies have shown that career planning has proven effective in improving career decision-making in vocational, junior high, and age students, but there has been no research that examines the relationship between career planning and career decision making in high school students. This study aims to determine the relationship between career planning and career decision making for high school students. The type of research used is quantitative research. The study population is students of class XII and aged from 17-19 years. The sampling technique used is a sampling quota with a total sample of 170 high school students. Data collection uses online media (google form) because the research was conducted during the Covid-19 pandemic. The career decision-making gauge consists of three aspects and 20 items with reliability is 0.974. The career planning measuring instrument consists of five aspects and 55 items with reliability is 0.938. Data analysis was performed with Pearson Correlation. The results of this study show that there is a strong and positive correlation between career planning and career decision making with the influence of career planning of 43.3%. That is, when students have good career planning, they will be able to make career decisions well. The results of this study can be a reference for the school to equip students with career planning programs, as well as a reference for students to prepare themselves with various information related to career planning. Hasil penelitian terdahulu menunjukkan bahwa perencanaan karir terbukti efektif meningkatkan pengambilan keputusan karir pada siswa SMK, SMP, dan usia pencari kerja, namun belum ada penelitian yang mengkaji hubungan antara perencanaan karir dan pengambilan keputusan karir pada siswa SMA. Penelitian ini bertujuan untuk mengetahui hubungan perencanaan karier dengan pengambilan keputusan karir siswa SMA. Tipe penelitian yang digunakan adalah penelitian kuantitatif. Populasi penelitian adalah siswa kelas XII dan berusia dari 17-19 tahun. Teknik sampling yang digunakan adalah kuota sampling dengan jumlah sampel sebanyak 170 orang siswa SMA. Pengumpulan data menggunakan media online (google form) karena penelitian dilakukan selama masa pandemi Covid-19. Alat ukur pengambilan keputusan karir terdiri dari tiga aspek dan 20 item dengan reliabilitas adalah 0,974. Alat ukur perencanaan karier terdiri dari lima aspek dan 55 item dengan reliabilitas adalah 0,938. Analisa data dilakukan dengan Pearson Correlation. Hasil penelitian ini menunjukkan bahwa terdapat korelasi yang kuat dan positif antara perencanaan karier dengan pengambilan keputusan karier dengan pengaruh dari perencanaan karier sebesar 43.3%. Artinya, ketika siswa memiliki perencanaan karir yang baik, maka akan dapat mengambil keputusan karir dengan baik. Hasil penelitian ini dapat menjadi rujukan bagi pihak sekolah untuk membekali siswa dengan program perencanaan karir, serta menjadi rujukan bagi siswa untuk mempersiapkan diri nya dengan berbagai informasi yang berkaitan dengan perencanaan karir.